Immune responses during and after exercise of constant and alternating intensity above the lactate threshold - Spanoudaki, S.a; Maridaki, M.a; Tsironi, M.b; Baltopoulos, G.c; Bogdanis, G.C.a; Baltopoulos, P.a (Journal of Sports Medicine and Physical Fitness, 2010)
{Aim. Intense and prolonged exercise greatly affects circulating cytokine levels. The purpose of this study was to investigate the possible changes in tumour necrosis factor -a (TNF-a), interleukin 6 (IL-6) and Cortisol concentrations during and after prolonged exercise of constant and alternating intensity of the same duration and total work performed. Methods. Ten male subjects underwent two main cycling exercise trials lasting one hour each. On one occasion, exercise intensity was alternated between 46.5±1.9% of maximal oxygen uptake (VO2max ) for 40 s and 120% of VO2max for 20 s, so that the mean intensity corresponded to 105% of the lactate threshold. On the other occasion, exercise intensity was constant at 105% of the lactate threshold. Levels of TNF-a, IL-6 after lipo polysaccharide (LPS) stimulation as well as Cortisol were measured at rest, 30 and 60 minutes of exercise and 1 hour after. Results. No significant differences were observed in TNF-a concentrations between the two exercise protocols (P= 0.75), but there was a significant time effect (P<0.01). TNF-a was increased in both groups from a resting value of 436.1±102.5 to 649.5±187.7 pg/mL (P<0.05) at the end of exercise and was subsequently decreased 1 hour post exercise to 305.9±78.8 pg/mL (P<0.01). No significant difference in IL-6 and Cortisol concentrations was observed between the two exercise protocols (P=0.13